2010
DOI: 10.1111/j.1399-3054.2010.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fast chlorophyll fluorescence rise (O-K-J-I-P) curves in green fruits indicates electron flow limitations at the donor side of PSII and the acceptor sides of both photosystems

Abstract: Limited evidence up to now indicates low linear photosynthetic electron flow and CO(2) assimilation rates in non-foliar chloroplasts. In this investigation, we used chlorophyll fluorescence techniques to locate possible limiting steps in photosystem function in exposed, non-stressed green fruits (both pericarps and seeds) of three species, while corresponding leaves served as controls. Compared with leaves, fruit photosynthesis was characterized by less photon trapping and less quantum yields of electron flow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…According to the recent view, O-J phase is related to the accumulation of Q À A , I-P is associated with PQ pool reduction while J-I is not related with reduction in the PQ pool (Gauthier et al 2010) while J-I phase was shown to be suppressed which affect the OEC (Schreiber and Neubauer 1987). The I-P amplitude in the transient has also been related to the relative size of the pools of final PS I electron acceptors (Kalachanis and Manetas 2010).…”
Section: Resultsmentioning
confidence: 99%
“…According to the recent view, O-J phase is related to the accumulation of Q À A , I-P is associated with PQ pool reduction while J-I is not related with reduction in the PQ pool (Gauthier et al 2010) while J-I phase was shown to be suppressed which affect the OEC (Schreiber and Neubauer 1987). The I-P amplitude in the transient has also been related to the relative size of the pools of final PS I electron acceptors (Kalachanis and Manetas 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Kotakis et al (2006) further showed that cyclic electron flow is enhanced (at the expense of the linear photosynthetic electron flow) in twig collenchyma to adjust potential ATP/NADPH ratios and/or to counteract the detrimental effects of hypoxia. This, combined with the increased activity of non-photochemical quenching via the xanthophyll cycle observed in apple (Cheng and Ma, 2004) and grapevine (Young et al, 2016), suggest that non-foliar photosynthesis is possibly required to produce ATP in organs where gas exchange is prevented (Kalachanis and Manetas, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence levels F o (50 μs), F K (300 μs), F J (2 ms), F I (30 ms), and F P (peak, about 300 ms) were recorded. The OJIP transient has become one of the most popular tools in photosynthetic research (Kalachanis and Manetas 2010;Pang et al 2012;Zhang et al 2011Zhang et al , 2012aZhang et al , 2012b. The shape of the OJIP transient is very sensitive to environmental stresses.…”
Section: Chlorophyll a Fluorescence (Ojip) Transient Measurementmentioning
confidence: 99%